1975
DOI: 10.1111/j.1545-5300.1975.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Addicts and Their Parents

Abstract: A minority of opiate addicts, especially young males, maintain close ties with their parents. These families, referred to here as “addict‐families,” are characterized by: (a) much greater success by the parents in meeting reality demands than by the addicts; (b) apparent congeniality and closeness but an absence of effective communication; (c) unsuccessful attempts by the parents to control the addict's behavior; (d) a tendency for the father to dominate the mother; (e) extreme overindulgence of the addict by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1
3

Year Published

1976
1976
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 14 publications
3
30
1
3
Order By: Relevance
“…One study that has implications similar to that of our own work was reported by Alexander and Dibb. (1) Our findings differ from theirs to a considerable extent. We find that a majority rather than a minority of those defined as either abusers or addicts maintain close ties with their families of origin and that a majority rather than a minority of families of addicts are open to being involved in therapy sessions.…”
Section: Drug Abuse In the Light Of Family Loyaltiescontrasting
confidence: 99%
“…One study that has implications similar to that of our own work was reported by Alexander and Dibb. (1) Our findings differ from theirs to a considerable extent. We find that a majority rather than a minority of those defined as either abusers or addicts maintain close ties with their families of origin and that a majority rather than a minority of families of addicts are open to being involved in therapy sessions.…”
Section: Drug Abuse In the Light Of Family Loyaltiescontrasting
confidence: 99%
“…Some studies have focused on adolescent drug abusers (Coleman, 1980;Egger et al, 1978;Kaufman & Kaufmann, 1979;Klagsbrun & Davis, 1977;Madanes et al, 1980;Schwartzman & Bokos, 1979), while others have used a retrospective approach with older addicts (Alexander & Dibb, 1975;Duncan, 1978;Graeven & Schaef, 1978;Stanton et al, 1978). Still other studies examine the re-creation of family-of-origin problems in the family-of-procreation (Harbin & Mazier, 1975;Seldin, 1972).…”
Section: The Family Dynamics Of Drug Abuse: An Overview and Some Limimentioning
confidence: 94%
“…This loss of family members is extended to those lost through immigration. Studies have long demonstrated that the children of immigrants have addictions at a rate three times that of the immigrants' generations (Rosenberg, 1969;Alexander and Dibb, 1975).…”
Section: Addiction and The Family Systemmentioning
confidence: 99%